2016
DOI: 10.1007/s11270-016-3153-z
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Soil Components on the Sorption of Chlorpyrifos

Abstract: It is generally assumed that the sorption of a nonionic pesticide on soil depends mainly on the content of soil organic matter (SOM); however, there are other factors that can contribute to this process. The possible causes of variation in the carbon-normalized partition coefficient (K OC ) for chlorpyrifos (CPF) for a diverse set of ten soils have been investigated. On the one hand, the analysis of the chemical composition of the SOM was analyzed, and on the other hand, the likely interactions between the org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The K oc value was used to estimate the potential mobility of OPs in soils. However, the report of wide variations in K oc values is common in the scienti c literature both between soils (Smernik and Kookana 2015, Ahangar et al 2008, Savini et al 2016) and between different isolated aggregate fractions (Bon eur et al 2016, Bonin andSimpson 2007). Many studies are devoted to elucidate the relative role of soil mineral and organic components to K oc variation with different model contaminants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The K oc value was used to estimate the potential mobility of OPs in soils. However, the report of wide variations in K oc values is common in the scienti c literature both between soils (Smernik and Kookana 2015, Ahangar et al 2008, Savini et al 2016) and between different isolated aggregate fractions (Bon eur et al 2016, Bonin andSimpson 2007). Many studies are devoted to elucidate the relative role of soil mineral and organic components to K oc variation with different model contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…As a multi-component and structurally organized combination, soil matrix contained different aggregates size organic-mineral complexes (Zhou, Liu and Tang 2004). Some studies have shown that the organicmineral interaction may block adsorbable functional groups on SOM surfaces, which changed con guration of SOM when associated with minerals and resulted in a negative contribution of minerals to OPs sorption by soils (Savini et al 2016 ). However, minerals may also positively contribute to OPs sorption in speci c soils as organic-mineral interaction highly exposed (He et al 2011).…”
Section: Introductionmentioning
confidence: 99%